2006
DOI: 10.3892/or.15.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Combined modality therapy of gemcitabine and irradiation on human glioma spheroids derived from cell lines and biopsy tissue

Abstract: Multicellular tumor spheroids have been used to examine aspects of combined modality treatment since they often recreate the in vivo tumor environment much more closely than other models. The radioenhancement by gemcitabine (dFdC) on human glioma spheroids derived from cell lines (CLS) and biopsy tissue, grown as organotypic multicellular spheroids (OMS), was studied. CLS of GaMg and U87 and OMS of four glioblastoma patients were used. Radiochemosensitvity was determined using migration and proliferation assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…These 3D tumor spheroids can be generated from both, established 2D cancer cell lines and fragments of tumor tissue. However, compared with 3D tumor spheroids derived from cancer cell lines, those derived from primary tumor tissues are better at mimicking the features of original tumors, such as tumor heterogeneity and complexity [3][4][5][6][7]. In addition, these primary tumor tissue-derived spheroids show some characteristics of cancer stem cells (CSCs) [1,7].…”
Section: Introductionmentioning
confidence: 98%
“…These 3D tumor spheroids can be generated from both, established 2D cancer cell lines and fragments of tumor tissue. However, compared with 3D tumor spheroids derived from cancer cell lines, those derived from primary tumor tissues are better at mimicking the features of original tumors, such as tumor heterogeneity and complexity [3][4][5][6][7]. In addition, these primary tumor tissue-derived spheroids show some characteristics of cancer stem cells (CSCs) [1,7].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, folate conjugated mesoporous silica nanoparticles have been reported in literature [17][18][19][20][21]. Herein, we designed a novel nanocarrier for targeting cancerous cells.…”
Section: Introductionmentioning
confidence: 97%
“…However, a study by Glicklis et al (Glicklis et al, 2004) has described that hepatocyte spheroids with diameters up to 100 μm have a good oxygenation status. Other studies by Fehlauer et al (Fehlauer et al, 2005;Fehlauer et al, 2006;Fehlauer et al, 2007) have reported that by using glioma spheroids with diameters of 200-250 μm, there are only few hypoxic cells and no central necrosis present.…”
Section: Hypoxia and Tumor Stem Cellsmentioning
confidence: 99%
“…However, in fact Kaaijk et al reported that proliferation in three investigated organotypic multicellular spheroids was decreased 7-20 fold relative to untreated controls one week after hypofractionated radiation with a total of 40 Gy. Moreover, Fehlauer et al (Fehlauer et al, 2005;Fehlauer et al, 2006) described in two studies a decrease in the percentage of MIB-1 positive proliferative cells in organotypic multicellular spheroids following irradiation with 20 Gy. It has also been suggested that tumor stem cells might show increased radioresistance compared to more differentiated cells Phillips et al, 2006;Rich, 2007).…”
Section: Primary Spheroids and Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation